The Current Approaches to the Transborder Studies in the Sphere of Tourism - Korneevets, Valentin S.; Kropinova, Elena G.; Dragileva, Irina I. (International Journal of Economics and Financial Issues, 2015)
The transborder relations have been intensively studied recently. The target of research depends on the specialization of the scientists involved in studying different aspects of transboundary ties. Depending on the aims, researchers elaborate on the notion of a transboundary region itself. The objective of our study is the consideration of approaches of different fields of study to the issues of transborder tourism; a search of innovative forms of transborder cooperation and identification of tools having a stimulating impact on the development of transborder tourism regions as a form of sustainable socio-economic development of transborder and border areas. Methods: comparative analysis, recreational and marketing approaches applied in tourism and recreational projecting of a space, and a cluster approach. The study resulted in the identification of the main areas of transborder and border cooperation; sets of issues were determined connected with studying transborder regions; properties characteristic of transborder regions were specified; major innovative tools were identified influencing the establishment of new transborder regions and clustering of the existing ones; and common regularities of tourism development in border regions were determined. Keywords: transborder tourism region, tourism resources, cross-border tourism, spatial planning in tourism, regional development, geographical aspects of tourism JEL Classifications: F5; L8; Z3